Kebijakan Moneter: Peran Bank Sentral Dalam Mengendalikan Inflasi - Rini Puji Astuti; Shinta Amelia Putri; Ahmad Samsudin (GLOBAL SCIENTS PUBLISHER, 2025)
Inflation, or the general rise in prices, is a big problem that can really hurt a country's economy. For Indonesia, a developing nation, keeping inflation under control is super important for steady economic growth and helping people get out of poverty. This study looks closely at how Bank Indonesia (our central bank) uses its policies to keep inflation in check and make sure our currency, the Rupiah, stays stable. We also explore how inflation affects Islamic banking, where fair and clear transactions depend on a stable currency. To do this research, we used a